(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
The Devonian Kess-Kess mounds, cropping out in the Hamar Laghdad Ridge (SE Morocco), provide a useful case-study for understanding the relationships between the microbial metabolic activities and micrite precipitation in an extreme environment. Very fine dark and white wrinkled laminae record microbial activity and the geochemistry of the organic matter allows the characterization of the source organisms. The biogeochemical characterization of extracted organic matter was performed through the functional group analyses by FT-IR Spectroscopy. FT-IR parameters indicate a marine origin and low thermal evolution for the organic material. The organic matter is characterized by the presence of stretching ?C=C vibrations attributable to alkene and/or unsaturated carboxylic acids. Preliminary analysis with GC-MS provides evidence for an autochthonous (<C22) organic matter source for the free carboxylic acids. The origin of short-chain fatty acids that have a marked even over odd C number predominance is attributable to bacteria and/or algae and they are similar to those recorded in recent (Black Sea) and ancient (Late Jurassic to Early Cretaceous) methane-seep microbialites. These biogeochemical signatures of microbial carbonate precipitation in an ancient extreme environment may have implications in astrobiological research considering the recent discovery of carbonate deposits on Mars.